Vulnerability of Agrobiodiversity and Agroforestry Settings to Climate Change in Gedeo Zone, Ethiopia - Fikadu Erenso; Azene Andemo (International Journal of Agronomy)
The study was carried out at the Gedeo zone aiming to investigate the vulnerability of agrobiodiversity and agroforestry settings to climate change in the district. Thus, the study was focused on evaluating crop diversity under different crop management practices and its distribution at the household level among different wealth classes and land use land cover change impact on agrobiodiversity and agroecosystems areas. Therefore, crop survey both from the home garden and crop field, the last 30 years’ data from five meteorological stations located in the district and the past 30 years’ Landsat satellite images at a 10-year interval within the same season was used. A total of 65 crop plant species with eleven major use categories have been recorded in the studied home gardens and crop fields. The crop plant species collected from both the home garden and crop field account for 57% and 38%, while the rest 5% were from the adjacent field. The land use and land cover map of the study area indicate that the largest part of the study area (108548.01 hectares) was covered by agroforestry, whereas the smallest portion of the district, about 975.15, 6457.41 and 12501.27 hectares of the area, was covered by bare land, cropland, and grassland, respectively. The remaining 20537.73 hectares (13.8%) of the district were covered with settlements. Crop species diversity is higher almost in the entire study site. However, crop species compositions were significantly variable among these study sites. The climatic data results indicated a reduction in average rainfall pattern in most of the stations and an increase in temperature within the employed time range.